Body image mediates the impact of pain on depressive symptoms in patients with systemic lupus erythematosus. (August 2019) - Gholizadeh, S; Azizoddin, D R; Mills, S D; Zamora, G; Potemra, H M K; Hirz, A E; Wallace, D J; Weisman, M H; Nicassio, P M
Objective: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease with treatment manifestations that can cause changes in appearance, including skin rashes, alopecia, vitiligo, and scars. SLE has been shown to adversely impact body image outcomes, and previous research has identified that greater disease activity is associated with worse body image outcomes which, in turn, are associated with greater depressive symptoms. For patients with SLE who also experience significant pain, poor body image outcomes may further compromise wellbeing and lead to greater depressive symptoms. The role of pain in body image has not been explored in SLE. Thus, the present study examined whether body image (specifically, body image-related quality of life) serves as a mediator of the relationship between pain and depressive symptoms among patients with SLE. Methods: Multiple mediation analysis was used to examine the hypothesis that body image-related quality of life mediates the relationship between pain and depressive symptoms in a sample of patients with SLE ( N  = 135) from an urban region in Los Angeles, California. Results: The sample was predominately female (92.6%) with a mean disease duration of approximately 17 years. Approximately one-quarter of the sample had elevated depressive symptoms. Body image-related quality of life was a significant mediator in the relationship between pain and depressive symptoms. The model accounted for 51% of the total variance in depressive symptoms ( R 2  = 0.51). Conclusion: This cross-sectional study suggested that body image-related quality of life may mediate the effects of pain on depressive symptoms among patients with SLE.